A Novel cis Regulatory Element Regulates Human XIST in a CTCF-Dependent Manner - Shah, Rini (Mol Cell Biol, 2021)
The long noncoding RNA XIST is the master regulator for the process of X chromosome inactivation (XCI) in mammalian females. Here, we report the existence of a hitherto-uncharacterized cis regulatory element (cRE) within the first exon of human XIST, which determines the transcriptional status of XIST during the initiation and maintenance phases of XCI. In the initiation phase, pluripotency factors bind to this cRE and keep XIST repressed. In the maintenance phase of XCI, the cRE is enriched for CTCF, which activates XIST transcription. By employing a CRISPR-dCas9-KRAB-based interference strategy, we demonstrate that binding of CTCF to the newly identified cRE is critical for regulating XIST in a YY1-dependent manner. Collectively, our study uncovers the combinatorial effect of multiple transcriptional regulators influencing XIST expression during the initiation and maintenance phases of XCI.